COPING STRESS PADA ORANG TUA ANAK DENGAN LEUKEMIA LIMFOSITIK AKUT(ALL) - Shanty Sudarji; Desy Lustiyani Wahono (Universitas Bunda Mulia, 2016)
Cancer is not a contagious disease but can cause death, especially in children. Cancer that primarily affects children is leukemia with the number of about 25 to 30% of all types of cancer that affects all children in Indonesia. Common type of leukemia in children is acute lymphocytic or lymphoblastic leukemia (ALL) with a percentage of 82% and acute myelocytic leukemia (AML) by 18%. The role of parents in caring for sick children ALL is not easy, a lot of problems that will occur during the care of children who ALL, either of themselves, their families and the environment. Coping with stress is necessary to handle problems that occur during the care for ALL children. Researchers conductedqualitative research with interviews of five parents who have children with acute lymphocytic leukemia. The data obtained showed that the main source of stress experienced came from a family that is the condition of a sick child, then the source of the stress from the environment and self. Symptoms of stressexperienced by the whole subject is prolonged fear and sadness. The whole subject S, RS, ME, DM, and NP using problem focused coping that are planful problem solving, seeking social support and coping confrontative. All subjects also use emotion focused coping. The whole subject of S, RS, ME, DM, and NPusing self control, accepting responsibility, and positive reappraisal. Only the subject of RS, ME, NP which uses distancing.